Antituberculosis activity, phytochemical identification of Costus speciosus (J. Koenig) Sm., Cymbopogon citratus (DC. Ex Nees) Stapf., and Tabernaemontana coronaria (L.) Willd. and their effects on the growth kinetics and cellular integrity of Mycobacterium tuberculosis H37Rv - Suriyati Mohamad; Nur Najihah Ismail; Thaigarajan Parumasivam; Pazilah Ibrahim; Hasnah Osman; Habibah A. Wahab (BMC, 2018)
Abstract Background Costus speciosus, Cymbopogon citratus, and Tabernaemontana coronaria are herbal plants traditionally used as remedies for symptoms of tuberculosis (TB) including cough. The aims of the present study were to evaluate the in vitro anti-TB activity of different solvent partitions of these plants, to identify the phytochemical compounds, and to assess the effects of the most active partitions on the growth kinetics and cellular integrity of the tubercle organism. Methods The in vitro anti-TB activity of different solvent partitions of the plant materials was determined against M. tuberculosis H37Rv using a tetrazolium colorimetric microdilution assay. The phytochemical compounds in the most active partition of each plant were identified using gas chromatography-mass spectrometry (GC-MS) analysis. The effects of these partitions on the growth kinetics of the mycobacteria were evaluated over 7-day treatment period in a batch culture system. Their effects on the mycobacterial cellular integrity were observed under a scanning electron microscope (SEM). Results The respective n-hexane partition of C. speciosus, C. citratus, and T. coronaria exhibited the highest anti-TB activity with minimum inhibitory concentrations (MICs) of 100-200 μg/mL and minimum bactericidal concentration (MBC) of 200 μg/mL. GC-MS phytochemical analysis of these active partitions revealed that majority of the identified compounds belonged to lipophilic fatty acid groups. The active partitions of C. speciosus and T. coronaria exhibited high cidal activity in relation to time, killing more than 99% of the cell population. SEM observations showed that these active plant partitions caused multiple structural changes indicating massive cellular damages. Conclusions The n-hexane partition of the plant materials exhibited promising in vitro anti-TB activity against M. tuberculosis H37Rv. Their anti-TB activity was supported by their destructive effects on the integrity of the mycobacterial cellular structure.